RECONSTRUCTION OF THE CONCEPT OF CORPORATE CRIMINAL LIABILITY IN ENVIRONMENTAL CRIMES: A PROGESIVE LEGAL STUDY AND ITS IMPLICATIONS FOR THE INDONESIAN CRIMINAL JUSTICE SYSTEM - Maruf, Asep Ammarudin (Jurnal Pacta Sunt Servanda, 2025)
Reconstructing the concept of corporate criminal liability is crucial due to the limitations of traditional approaches that are unable to address the complexity of today's environmental crimes. The reconstruction process includes restructuring basic concepts, adjusting evidentiary methods, developing more innovative sanctions, and implementing principles of environmental justice. The legal impact of this reconstruction is multi- layered, including changes to the criminal justice system, strengthening environmental law enforcement efforts, and adjusting regulations. The development of the concept of corporate criminal liability based on progressive legal theory has resulted in a more flexible and responsive framework. Corporate criminal liability in the environmental context is regulated by Article 116 paragraphs (1), (2), Article 117, and Article 118 of Law Number 32 of 2009 concerning Environmental Protection and Management. The legal impact of this reconstruction is multi-layered, encompassing changes to the criminal justice system, strengthening environmental law enforcement mechanisms, changes to institutional structures, and regulatory adjustments. The successful implementation of this reconstructed concept depends heavily on the commitment and collaboration of all parties involved in creating a more efficient and equitable environmental law enforcement system. Keywords: Reconstruction, Criminal Liability, Environmental Crimes, Progressive Law of the Criminal Justice System.